Hubungan Frekuensi Pangan Tinggi Purin, Aktivitas Fisik Dan Status Gizi Dengan Kadar Asam Urat Pada Pra Lansia Di Cikarang Barat - Septianingrum, Deanisa; Sabrina, Sabrina; Fikri, Al Mukhlas (Jurnal Ilmiah Wahana Pendidikan, 2024)
Gout is a non-communicable disease caused by several factors, such as excessive intake of high purine, obesity and kidney disorders. Pre elderly age has a risk of gout, especially in women due to menopause. Purpose : The purpose of this study was to analyze the correlation of food consumption frequency high in purine, physical activity and nutritional status with levels of uric acid on pre elderly. Materials and Methods : Analytical observational research with cross sectional design and purposive sampling technique. Tools and materials use the Easy Touch GCU Meter Device to check uric acid levels, Food Frequency Questionnaire (FFQ) forms, International Physical Activity Questionnaire (IPAQ) forms, as well as direct measurements with digital body scales and height to determine the nutritional status of pre elderly. The subjects in this study were pre elderly aged 45-59 years, number 74 subjects, male and female, who resided in the West Cikarang Region. Result : The results of the statistical test between consumption of food with high purin and nutritional status were obtained ρ values 0,009 and 0,000 <0,05. Then the results of the analysis of moderate food consumption and physical activity are obtained ρ values 0,125 and 0,063 > 0,05. Conclusion : There is a significant relationship between high purine food consumption and nutritional status with uric acid levels and there is no meaningful relationship between moderate consumption of purine foods and physical activity with uric acid levels. Advice that can be taken is the importance of early health checks by checking uric acid levels, maintaining a diet and controlling nutritional status. For the next research, education can be involve stakeholders to improve the high purine intake and nutritional status of pre elderly or older people.